CONGENITAL RUBELLA SYNDROME IN EARLY INFANCY: DIAGNOSTIC INSIGHTS AND CLINICAL TRENDS FROM A PAKISTANI COHORT (Journal of Medical & Health Sciences Review, 2025)
Background:Congenital Rubella Syndrome (CRS) remains a significant public health concern in countries with inadequate rubella vaccination coverage. Regardless of global development toward rubella control, limited data are available from Pakistan, specifically concerning the clinical profile and laboratory-confirmed occurrence of CRS in infants. To determine the frequency of laboratory-confirmed CRS among suspected infants and to illustrate the related clinical features at a tertiary care hospital in Karachi, Pakistan.Methods:A cross-sectional study was conducted at the Department of Pediatrics, Civil Hospital Karachi on 140 infants under 12 months of age. Suspected infants of having CRS based on clinical criteria, were enrolled using non-probability consecutive sampling. Clinical features including cataract, congenital heart disease, hepatosplenomegaly, jaundice, and microcephaly were recorded. Blood samples were collected and tested for rubella-specific IgM in infants